Long-term treated HIV infection is associated with platelet mitochondrial dysfunction - Wouter A. van der Heijden (Nature Portfolio, 2021)
Abstract HIV infection and antiretroviral therapy have been linked to mitochondrial dysfunction. The role of platelet mitochondrial dysfunction in thrombosis, immunoregulation and age-related diseases is increasingly appreciated. Here, we studied platelet mitochondrial DNA content (mtDNApl) and mitochondrial function in people living with HIV (PLHIV) and related this to platelet function. In a cohort of 208 treated PLHIV and 56 uninfected controls, mtDNApl was quantified, as well as platelet activation, platelet agonist-induced reactivity and inflammation by circulating factors and flow cytometry. In a subgroup of participants, the metabolic activity of platelets was further studied by mitochondrial function tests and the Seahorse Flux Analyzer. PLHIV had significantly lower mtDNApl compared to controls (8.5 copies/platelet (IQR: 7.0–10.7) vs. 12.2 copies/platelet (IQR: 9.5–16.6); p < 0.001), also after correction for age, sex and BMI. Prior zidovudine-use (n = 46) was associated with a trend for lower mtDNApl. PLHIV also had reduced ex vivo platelet reactivity and mean platelet volume compared to controls. MtDNApl correlated positively with both platelet parameters and correlated negatively with inflammatory marker sCD163. Mitochondrial function tests in a subgroup of participants confirmed the presence of platelet mitochondrial respiration defects. Platelet mitochondrial function is disturbed in PLHIV, which may contribute to platelet dysfunction and subsequent complications. Interventions targeting the preservation of normal platelet mitochondrial function may ultimately prove beneficial for PLHIV.